132 Does the use of a patient passport improve patient care in MND? A qualitative study. Issue 12 (14th November 2019) - Abdelgalil, Reem; Gaur, Akshay; Hewamadduma, Channa
Abstract : Background: Care provision for Motor Neurone Disease (MND) patients require a Multidisciplinary Team (MDT) approach. Healthcare Professionals (HCPs) and MND patients often find it challenging to communicate effectively. Communication is particularly difficult and discontinuous in patients with rapidly changing conditions such as MND. Patient Passports (PP) can be used as a tool to improve communication and patient experience. We studied the place of PP in MND care. Aim: To explore the views of MND patients and staff involved in MND care regarding the use of PP. Methods: MND patients (n=35) and staff involved in MND care were consulted using semi-structured interviews and focus group discussions. Results: Overall, themes emerged overwhelmingly favoured the use of a MND passport. These include improvement in communication, standardising healthcare provision across different regions and allowing for greater coordination of care. The emergency care providers and community HCP felt the PP was paramount to communicate with the parent team. However, concern was raised for the need to tailor it to the patient. Conclusion: The PP was recognised as a distinct need. However, to validate the above findings, wider MND patient/carer and HCP survey is necessary.